2012
DOI: 10.4995/wrs.2012.1035
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter concentrations and emissions in rabbit farms

Abstract: AbstrAct:The extent of the potential health hazards of particulate matter (PM) inside rabbit farms and the magnitude of emission levels to the outside environment are still unknown, as data on PM concentrations and emissions in and from such buildings are scarce. The purpose of this study was to quantify airborne PM10 and PM2.5 (particulate matter which passes through a size-selective inlet with a 50% efficient cut-off at 10 µm aerodynamic diameter or at 2.5 µm aerodynamic diameter, respectively) concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…In this study, we calculated the volumetric CO 2 production at the house level by the values given by , which are composed of the metabolic CO 2 -production by the animal multiplied by a factor 1.1 for the contributions of manure and litter, provided that the manure is removed frequently (i.e., every three weeks) and the litter is not of the deep-litter type (i.e., <0.5 m). Recent studies in broilers where manure was replaced by fresh bedding material between growth cycles, showed that the contribution of the litter to the total CO 2 -production increased exponentially from negligible levels during the first 4 weeks to values between 8 and 20% at the end of the growth cycle (Calvet et al, 2011;Calvet et al, 2012). In a high-rise cage house, Liang et al (2005) measured the CO 2 -production from manure that had accumulated for 6 months and found that it contributed 5 to 9% to the total CO 2 -production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we calculated the volumetric CO 2 production at the house level by the values given by , which are composed of the metabolic CO 2 -production by the animal multiplied by a factor 1.1 for the contributions of manure and litter, provided that the manure is removed frequently (i.e., every three weeks) and the litter is not of the deep-litter type (i.e., <0.5 m). Recent studies in broilers where manure was replaced by fresh bedding material between growth cycles, showed that the contribution of the litter to the total CO 2 -production increased exponentially from negligible levels during the first 4 weeks to values between 8 and 20% at the end of the growth cycle (Calvet et al, 2011;Calvet et al, 2012). In a high-rise cage house, Liang et al (2005) measured the CO 2 -production from manure that had accumulated for 6 months and found that it contributed 5 to 9% to the total CO 2 -production.…”
Section: Resultsmentioning
confidence: 99%
“…Oscillating Microbalance (TEOM) has been used by research groups in Spain (Adell et al, 2012;, the UK , and the USA S. Li et al, 2011;Ni et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Opfokhennen en hanen van legrassen, <18 wk [2] Emissie PM10 Konijnen In een artikel worden PM10 emissies gerapporteerd van 14,9 mg/dag per dierplaats voor voedsters en 5,99 mg/dag per dierplaats voor vleeskonijnen. 49 Deze waarden zijn equivalent aan respectievelijk (14,9 × 10 -3 × 365 dagen =) 5,4 g/jaar per dierplaats en (5,99 × 10 -3 × 365 dagen =) 2,2 g/jaar per dierplaats.…”
Section: ) Endotoxine Gehalte In Pm10unclassified
“…In fact, culture based methods can underestimate the microbial count by a factor of 10-200 times in comparison to nonculture methods (Chi and Li, 2005). Studies investigating microbial count from livestock buildings have reported the total bacterial and fungal count, specific genera and different species count both by culture and non-culture methods (Agranovski et al, 2007;Vucemilo et al, 2008;Oppliger et al, 2008;Rinsoz et al, 2008;Adell et al, 2012;De Roy et al, 2012;Liang et al, 2013;Muller and Nebe-von-Caron, 2010;Nonnenmann et al, 2010;Rubbens et al, 2017). A range of bacterial and fungal counts are reported in different studies in poultry houses and other livestock units (Agranovski et al, 2007;Vucemilo et al, 2008;Oppliger et al, 2008;Lonc and Plew, 2011), suggesting spatiotemporal and seasonal variability in emission from poultry houses (Wojcik et al, 2010).…”
Section: Introductionmentioning
confidence: 99%